A Convenient and Stable Heterogeneous Nickel Catalyst for Hydrodehalogenation of Aryl Halides Using Molecular Hydrogen. Issue 5 (27th January 2022) - Leonard, David K.; Ryabchuk, Pavel; Anwar, Muhammad; Dastgir, Sarim; Junge, Kathrin; Beller, Matthias
Abstract: Hydrodehalogenation is an effective strategy for transforming persistent and potentially toxic organohalides into their more benign congeners. Common methods utilize Pd/C or Raney‐nickel as catalysts, which are either expensive or have safety concerns. In this study, a nickel‐based catalyst supported on titania (Ni‐phen@TiO2 ‐800) is used as a safe alternative to pyrophoric Raney‐nickel. The catalyst is prepared in a straightforward fashion by deposition of nickel(II)/1, 10‐phenanthroline on titania, followed by pyrolysis. The catalytic material, which was characterized by SEM, TEM, XRD, and XPS, consists of nickel nanoparticles covered with N‐doped carbon layers. By using design of experiments (DoE), this nanostructured catalyst is found to be proficient for the facile and selective hydrodehalogenation of a diverse range of substrates bearing C−I, C−Br, or C−Cl bonds (>30 examples). The practicality of this catalyst system is demonstrated by the dehalogenation of environmentally hazardous and polyhalogenated substrates atrazine, tetrabromobisphenol A, tetrachlorobenzene, and a polybrominated diphenyl ether (PBDE). Abstract : The big reveal : Hydrodehalogenation of 35 different aryl halides (Ar−I, Ar−Br, and Ar−Cl) is performed using a heterogeneous nickel catalyst (Ni‐phen@TiO2 ‐800) and molecular hydrogen. This work represents an effective strategy for converting thermally and chemically inert hazardous compounds into their less noxious congeners. Characterization of the catalyst reveals nickel nanoparticles covered with N ‐doped carbon layers.